Abortion in the world: statistical-epidemiological update regarding legally registered abortion. - Spaziante, Ermenegildo (Medicina e Morale, 1998)
The comparison between the statistical data concerning legally registered abortion, shows that among the indexes of abortion referred for 1995 and 1996, 25 countries presented variations compared with the previous year. For the above mentioned countries, a total of 8.857.953 abortions were registered in 1995 and a total of 6.014.649 abortions were registered in 1996, with a difference of 2.843.304 which is a decrease of 32.09%. The countries with the greatest decrease of abortions were Poland (60.7% less), Russia (46.6% less), the Czech republic (44.0% less) and Romania (15.3% less). The greatest increase was recorded in Estonia (43.6% more), in Kyrgyzstan (20.4% more), Holland (7.7% more) and Greece (7.8% more). As for the index of abortions referred to the number of live born infants in the same year, the greatest variations were recorded in Russia, Romania, Hungary and Poland. The most important increase of the index of abortions referred to 100 live born infants was recorded in Estonia, Bugaria and Latvia.